Evaluation of the Xinjiang indigenous fruits Xiaobai apricots: Chemical and nutritional studies - Lin Chen; Rui Tang; Jianlin Zhang; Qian Li; Dandan Fang; Luxi Jiang; Buhailiqiemu Abudureheman; Xingqian Ye (Journal of Agriculture and Food Research)
The fresh fruits, dried kernels and nuts of Xiaobai apricot is popular in Xinjiang, but the comparative research about chemical and nutritioninal component has been relatively limited. In this study, the proximate composition, volatile organic compounds, total phenolic content (TPC), and total flavonoid content (TFC), as well as the antioxidant capacity of fresh fruits, dried kernel and nuts of Xiaobai apricot were examined using ICP-MS, HPLC and GC-MS. The protein, fat and rude fiber contents of nuts were significantly higher than fresh fruits and dried kernels. The fresh fruits showed higher contents of K (178000 ± 100 mg/100 g d m.), Na (2100 ± 100 mg/100 g d m.), Mg (5700 ± 100 mg/100 g d m.), P (10000 ± 100 mg/100 g d m.) and Cu (500 ± 50 mg/100 g d m.). The organic acids of malic, fumaric, and acetic constitute the primary organic acids for the three samples. The fatty acid content of nuts was higher than fresh fruits and dried kernels. The highest concentrations of oleic acid (MUFA) was found in nuts (16.69 ± 0.94 mg/100 g). Ten amino acids of 17 kinds showed higher levels, the highest content showed in aspartic acid as 2400 mg/100 g. In the fresh fruits, dried kernels and nuts, 58, 9 and 6 volatile organic compounds were identified, respectively. The nuts of Xiaobai apricot contain a higher concentration of TPC and TFC than dried kernels and fresh fruits. These results provide a scientific basis for the industrial production of dried apricots and nuts, the fresh fruits of Xiaobai apricot can be used as nutritional supplements.